Imaging the impurity distribution in glacier ice cores with LA-ICP-MS. Issue 10 (3rd August 2020) - Bohleber, Pascal; Roman, Marco; Šala, Martin; Barbante, Carlo
Abstract : The novel combination of ice core LA-ICP-MS with improved imaging techniques reveals impurity localization without artifacts. Abstract : Impurity records in polar ice cores have provided invaluable insights into atmospheric aerosol concentrations of the past environment. The investigation of the oldest, deepest and highly thinned ice core layers is one of the most pressing tasks in today's state-of-the-art ice core research. This calls for impurity analysis at high spatial resolution, which has to take into account post-depositional processes through the interaction of impurities with the ice matrix. To this end, the technique of laser ablation inductively-coupled plasma mass spectrometry (LA-ICP-MS) has shown great potential, which still remains to be fully exploited, however. Here we demonstrate how the application of LA-ICP-MS for imaging the impurity distribution in ice cores can be refined and strongly improved. A novel cryogenic two-volume ablation chamber is paired with a rapid aerosol transfer system in order to achieve fast washout times (34 ms). In so doing, we are able to analyze ice cores for the first time using next generation LA-ICP-MS imaging techniques. The improved LA-ICP-MS method for ice cores offers not only high scan speeds for single line profiles (around 1 mm s −1 ) but can also map the localization of impurities at high spatial resolution (35 μm), at high speed and without imaging artifacts. This promises not only new insights into the impurity distribution in glacier ice but also lays the ground for an improved understanding of the LA-ICP-MS signal obtained from ice cores. As a result, LA-ICP-MS can deliver an important contribution for retrieving future paleo-environmental records from highly thinned ice layers.